The expression of GCN5, HDAC1 and DNMT1 in parthenogenetically activated mouse embryos. (February 2015) - Peng, M.; Li, Y.; Huang, H.; Jin, F.
Abstract The functions and mechanisms of the genomes from the different gametes on the epigenetic reprogramming of embryos are still unclear. In this study, the expression of enzymes typically associated with changes in epigenetic markers was measured in parthenogenetically-activated and in-vitro fertilised embryos. General control of nucleotide synthesis 5 (GCN5), histone deacetylase 1 (HDAC1) and DNA methyltransferases 1 (DNMT1), were analysed in early diploid PA and control embryos using fluorescent immunocytochemistry. Levels of GCN5 expression of two-cell embryos were similar between the PA and IVF groups, but the distribution of GCN5 in PA embryos at the four-cell stage was significantly decreased. HDAC1 and DNMT1 expression was also significantly decreased in PA embryos. In addition, the observed localisation of HDAC1 expression within and surrounding the nucleus in IVF embryos was not present in PA embryos. Embryos with only the maternal genome have altered expression patterns of key enzymes required for embryonic epigenetic reprogramming.